(untitled) (Global Journal of Human-Social Science, 2018)
This article attempts at integrating core socialist elements analyzed through the prism of Castoriadis s and Wright s work into a model of open cooperativism between Commons-based peer production ethical market entities and a partner state introduced by Bauwens and Kostakis It concludes with a critical appraisal of Bauwens and Kostakis s model